Effects of a level-based immersive virtual reality physical therapy program on static and dynamic balance in Parkinson’s disease: Protocol for a randomized controlled trial - Lorena Morcillo-Martínez; María Sanz-Mármol; Adriana Isabel Romanos-Navarrete; Sandra Calvo; Lilian Le Roux-Ethève; Laura Esteban-Repiso; Paula Córdova-Alegre; Carolina Jiménez-Sánchez; Aitor Garay-Sánchez; Natalia Brandín-de la Cruz (PLoS ONE, 2026)
Background Parkinson’s disease (PD) is a neurodegenerative disorder characterized by postural instability, which significantly contributes to an increased risk of falls (occurring in 45–68% of persons with PD annually), leading to greater functional dependence, social isolation, and a significant decrease in quality of life. The aim of this randomized clinical trial is to evaluate the effects of an immersive virtual reality (IVR) intervention on static and dynamic balance, gait speed, functional mobility, lower limb strength, and quality of life in people with PD. Furthermore, the study will assess treatment adherence, participant satisfaction, as well as the potential occurrence of adverse effects associated with the application of IVR. Methods A 10-month, single-blind, two-arm randomized controlled trial will be conducted with participants aged 55–90 years diagnosed with PD and classified between stages 2.5 and 4 on the modified Hoehn and Yahr scale. Participants will be randomly assigned to one of two groups: an experimental group and a control group. The intervention will consist of an 8-session program. The first part of each session, common to both groups, will include a standardized strength training program. In the second part, the experimental group will receive a physical therapy balance program using IVR, while the control group will follow a usual physical therapy balance exercise program. Discussion This study will examine whether IVR can improve static and dynamic balance rehabilitation in Parkinson’s disease beyond usual physical therapy, addressing real-world motor and dual-task challenges. By providing enriched sensory input and adaptive tasks, the IVR seeks to optimize motor learning and functional mobility. Demonstrating safety and clinically meaningful improvements would support IVR as a scalable and engaging tool to reduce risk of falls and enhance quality of life in PD. Trial registration ClinicalTrials.gov NCT07274514